Mitochondrial DNA from endothelial cells activated the cGAS-STING pathway and regulated pyroptosis in lung ischaemia reperfusion injury after lung transplantation - Ying-nan Ju; Hu Li; Zi-peng Zhuo; Qing Yang; Wei Gao (Immunobiology)
Objective: Cell dysfunction and death induced by lung ischaemia–reperfusion injury (LIRI) are the main causes of death in transplant patients. Activation of the cGAS-STING-induced immune response and death plays a critical role in multiple organ injuries. However, no study has yet investigated the role of the cGAS-STING pathway in LIRI after lung transplantation. Methods: Sprague-Dawley (SD) rats were subjected to left lung transplantation and administered inhibitors of cGAS and STING. The expression of cGAS-STING-TBK1-IRF3, histological injury, pulmonary permeability, and the levels of cytokines and pyroptotic proteins in transplanted lungs were tested. Endothelial cells were subjected to hypoxemia and reoxygenation and treated with inhibitors of cGAS and STING. Mitochondrial DNA (mtDNA), the cGAS-STING axis and cytokine levels in cells, cellular activity and death were evaluated. Moreover, after the administration of deoxyribonuclease (DNase) I, the reoxygenated endothelial cells were also examined for cellular function and inflammatory factor expression. Finally, we administered an agonist of STING and an inhibitor of cathepsin B to the normal endothelium and investigated pyroptosis and pyroptotic proteins. Results: After 24 h of reperfusion, the expression of cGAS-STING-TBK1-IRF3 and pyroptotic proteins was significantly increased, and inhibitors of cGAS or STING ameliorated lung injury and reduced pyroptotic protein levels. In vitro, the inhibition of cGAS and STING reduced the activation of TBK and IRF3 and reduced cellular injury and death. The activation of cGAS-STING and cellular inflammation were suppressed by DNase I. Cathepsin B and NLRP3 were upregulated by an agonist of STING, and an inhibitor of cathepsin B reduced NLRP3 levels. Conclusion: cGAS-STING participated in LIRI by promoting endothelial cell pyroptosis via cathepsin B.